2010
DOI: 10.1080/14634988.2010.526439
|View full text |Cite
|
Sign up to set email alerts
|

Macro-invertebrate species diversity as a potential universal measure of wetland ecosystem integrity in constructed wetlands in South East Melbourne

Abstract: The use of macroinvertebrates in the assessment of wetland ecosystem integrity is an increasingly common tool used for management and conservation. The sensitivity of macroinvertebrates to ecological fluctuation makes them reliable and appealing indicators of ecosystem integrity. However, there is little or no published data available for assessment of wetland ecosystem integrity on the basis of macroinvertebrate species diversity in constructed wetlands of metropolitan Melbourne. The aim of the following stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The composition of macro-invertebrate communities reflects the quality of aquatic ecosystems (Roldán-Pérez 2016). Some attributes such as species richness (Awal and Svozil 2010), total family richness (Ortega et al 2004), total macro-invertebrate abundance and taxon richness (Stewart and Downing 2008) have been used to evaluate the integrity of wetlands. After testing 50 combinations of relative invertebrate densities, Lunde and Resh (2012) found that only eight taxa were useful: Ephemeroptera, Odonata, Trichoptera, Tanypodinae, Chironomidae, Oligochaeta and Coleoptera.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of macro-invertebrate communities reflects the quality of aquatic ecosystems (Roldán-Pérez 2016). Some attributes such as species richness (Awal and Svozil 2010), total family richness (Ortega et al 2004), total macro-invertebrate abundance and taxon richness (Stewart and Downing 2008) have been used to evaluate the integrity of wetlands. After testing 50 combinations of relative invertebrate densities, Lunde and Resh (2012) found that only eight taxa were useful: Ephemeroptera, Odonata, Trichoptera, Tanypodinae, Chironomidae, Oligochaeta and Coleoptera.…”
Section: Introductionmentioning
confidence: 99%
“…Chironomidae and Corixidae were amongst the dominant families recorded in a previous study of constructed wetlands in south eastern Melbourne by Awal and Svozil (2010). They suggested that these taxa were likely to be common in constructed water bodies Table 1. throughout the Melbourne region, and considered this to be a response to nutrient enrichment created by stormwater inflows.…”
Section: Discussionmentioning
confidence: 96%
“…Tolerant taxa typically found in such environments include chironomid midges and oligochaete worms and a range of taxa associated with the water surface film (Batty et al, 2005;Pankratz et al, 2007;O'Connor et al, 2012). Even if water quality targets are reached, the abundance of invertebrates is often lower in constructed wetlands than in natural wetlands (Batty et al, 2005;Awal and Svozil, 2010;Briers, 2014). In addition to water quality, suitability of habitat can also determine the presence of macroinvertebrate taxa in wetland systems (Mereta et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…They are (i) taxonomically/ecologically well-understood, (ii) easily sampled, (iii) easily identified, (iv) continually exposed to natural or anthropogenic disturbances when they occur, (v) known to integrate episodic or cumulative water quality impacts in time and space and often show predictable responses to these disturbances, and (vi) known to have strong ecological relationships with other target groups such as fish (Noss 1990;Pearson 1994;Burton et al 1999;Heino et al 2009;Uzarski et al 2017). In wetlands, macroinvertebrates have been previously used as bioindicators of eutrophication (Chessman et al 2002), impacts of mining activities (Thomas and John 2006), ecological condition of constructed wetlands (Awal and Svozil 2010), and general urban and agricultural development in watersheds (Gezie et al 2017).…”
Section: Introductionmentioning
confidence: 99%